2D Group IVB Transition Metal Dichalcogenides. (5th August 2018) - Yan, Chaoyi; Gong, Chuanhui; Wangyang, Peihua; Chu, Junwei; Hu, Kai; Li, Chaobo; Wang, Xuepeng; Du, Xinchuan; Zhai, Tianyou; Li, Yanrong; Xiong, Jie
Abstract: Semiconductor technology is currently impaired by the surface dangling bond of materials, which introduces scattering and interface traps. 2D materials, especially transition metal dichalcogenides (TMDs) with different main groups, have settled this issue by utilizing unique atomically smooth surfaces and van der Waals (vdW) structures. Over the past few decades, many processes for exploring new materials, manipulating physical properties, and synthesizing single crystals have been developed. Among these 2D materials, group IVB TMDs are distinguished for their splendid physical properties, including ultrahigh mobility, charge density wave, superconducting transitions, etc. Here, the recent advances in group IVB TMDs are reviewed, which offer easy access to next generation nano‐, opto‐, thermal‐electronic, energy storage and conversion applications. Both the advantages and challenges of these studies are summarized to further clarify existing problems. Abstract : 2D group IVB transition metal dichalcogenides (TMDs) are distinguished for their splendid properties and potential applications in next generation nano‐, opto‐, thermal‐electronic, energy storage and conversion. This article reviews the recent studies on their properties correlating to crystal and electronic structures, various applications, and synthesis methods. Both the advantages and challenges of these materials are summarized for further development.